2017
DOI: 10.1038/s41598-017-18071-w
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of ceramide and ceramide analogs against pathogenic Neisseria

Abstract: Certain fatty acids and sphingoid bases found at mucosal surfaces are known to have antibacterial activity and are thought to play a more direct role in innate immunity against bacterial infections. Herein, we analysed the antibacterial activity of sphingolipids, including the sphingoid base sphingosine as well as short-chain C6 and long-chain C16-ceramides and azido-functionalized ceramide analogs against pathogenic Neisseriae. Determination of the minimal inhibitory concentration (MIC) and minimal bactericid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 61 publications
2
52
0
Order By: Relevance
“…Sphinganine belonging to sphingosines and sphingolipids was identified in the isolated strain SK1. Previous studies have demonstrated that several sphingoid bases and fatty acids act as antimicrobial agents [54,55]. Tetrodotoxin (TTX) is a strong marine toxin which is a powerful sodium channel inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Sphinganine belonging to sphingosines and sphingolipids was identified in the isolated strain SK1. Previous studies have demonstrated that several sphingoid bases and fatty acids act as antimicrobial agents [54,55]. Tetrodotoxin (TTX) is a strong marine toxin which is a powerful sodium channel inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…At present, it is unknown how sphingosine kills bacteria. It is known that micellar sphingosine kills many pathogens including E. coli , P. aeruginosa , S. aureus , A. baumannii , Moraxella catarrhalis , Haemophilus influenzae , Burkholderia cepacia , Neisseria meningitides , and Neisseria gonorrhoeae [1015, 25]. It is possible that sphingosine simply kills pathogens by its biophysical properties, which would also suggest that sphingosine’s antimicrobial mechanism is not prone to development of bacterial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism of sphingosine's bactericidal effect has not yet been fully resolved in detail. It is known that micellar sphingosine kills many pathogens including Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Acinetobacter baumannii, Moraxella catarrhalis, Haemophilus influenzae, Burkholderia cepacia, Neisseria meningitides, and Neisseria gonorrhoeae [9,[29][30][31][32][33][34]. It is possible that sphingosine simply kills pathogens by its biophysical properties, which would also suggest that sphingosine's antimicrobial mechanism is not prone to the development of bacterial resistance.…”
Section: Discussionmentioning
confidence: 99%